Adapting tourism promotion during crisis: a visual content analysis of Portugal's Instagram strategy amid Covid-19 - Corrêa, Cynthia; Alves, Helena Maria Baptista; Estevão, Cristina Maria Santos (Investigaciones Turísticas, 2025)
The image of a destination is an important element in the traveler’s decision-making process, yet it is highly susceptible to disruption during critical events such as the COVID-19 pandemic. Despite growing interest in this topic, a gap remains in the literature regarding how Destination Management Organizations (DMOs) leverage social media to shape destination image, promote their brands, and reposition themselves during periods of uncertainty. Using Portugal as a case study, this research addresses this gap by investigating how the country’s DMO employed Instagram to project its destination image during the COVID-19 pandemic and examines the patterns of user engagement with this content. A mixed-methods approach has been used, beginning with a visual content analysis of 763 Instagram photographs published by Portugal’s DMO between 2019 and 2021. These photos were categorized into predefined patterns and themes, covering three phases of the pandemic (pre-lockdown, lockdown, and post-lockdown). Quantitative analyses of associations and mean differences were then conducted to explore the adaptive strategies of the DMO and user engagement over time. The findings reveal that the DMO’s promotional strategy centered on nature and landscape attributes, highlighting Portugal's natural beauty to evoke interest and inspire visits. During the lockdown, the DMO adapted its strategy by reducing posts featuring people, outdoor activities, gastronomy, and cultural elements. Notably, user engagement on Instagram increased during the lockdown phase compared to the pre- and post-lockdown periods. Engagement analysis also indicates particular interest in gastronomy, culture, and art, highlighting the growing significance of tourist experiences and local lifestyles in tourism activities. However, preferences shifted away from depictions of social interactions, crowded spaces, and leisure activities during the critical crisis period, aligning with the DMO's strategies. This study contributes to the literature and offers practical implications for optimizing engagement and reinforcing destination image through strategic social media used in challenging contexts.